2012
DOI: 10.1007/978-94-007-5416-4_16
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is the most common age-related motoric neurodegenerative disease initially described in the 1800’s by James Parkinson as the ‘Shaking Palsy’. Loss of the neurotransmitter dopamine was recognized as underlying the pathophysiology of the motor dysfunction; subsequently discovery of dopamine replacement therapies brought substantial symptomatic benefit to PD patients. However, these therapies do not fully treat the clinical syndrome nor do they alter the natural history of this disorder m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
203
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 335 publications
(222 citation statements)
references
References 423 publications
(531 reference statements)
2
203
0
6
Order By: Relevance
“…It greatly affects the quality of life of patients (Zhang et al, 2016). Incidence of PD disease is approximately 1.8 times higher in men versus women (1.5-2.0) (Hirtz et al 2007;Mhyre, et al, 2012). The study of Zhang et al, 2016 revealed that the incidence of PD is slightly higher in males than in females; the ratio was close to 1:1, the average age of PD patients was about 60 years, the education level of patients with PD was paralleled with that of age-matched (40-70 years old) (Ransmayr, 2015), and education is not an associated factor for PD.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It greatly affects the quality of life of patients (Zhang et al, 2016). Incidence of PD disease is approximately 1.8 times higher in men versus women (1.5-2.0) (Hirtz et al 2007;Mhyre, et al, 2012). The study of Zhang et al, 2016 revealed that the incidence of PD is slightly higher in males than in females; the ratio was close to 1:1, the average age of PD patients was about 60 years, the education level of patients with PD was paralleled with that of age-matched (40-70 years old) (Ransmayr, 2015), and education is not an associated factor for PD.…”
Section: Introductionmentioning
confidence: 99%
“…The study of Zhang et al, 2016 revealed that the incidence of PD is slightly higher in males than in females; the ratio was close to 1:1, the average age of PD patients was about 60 years, the education level of patients with PD was paralleled with that of age-matched (40-70 years old) (Ransmayr, 2015), and education is not an associated factor for PD. The socioeconomic burden of PD is great with estimates of both direct and indirect costs upward of about $23 billion every year in the US (Huse et al 2005;Mhyre, et al, 2012). Age is the single greatest risk factor for PD with the number of world-wide cases increasing from an estimated 4.1 million (340,000 US cases) in 2005 to nearly 8.7 million (610,000 US cases) by 2030 (Dorsey et al 2007;Mhyre, et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Characterized clinically by resting tremor, bradykinesia, rigidity, and postural instability. [4] The pathological hallmark of the illness is a relatively selective degeneration of the neuromelanin-pigmented dopaminergic neurons of the substantia nigra pars compacta coupled with the formation of intracytoplasmic protein aggregates known as Lewy bodies. [5,6] Progressive loss of dopaminergic neurons is a feature of normal aging; however, symptoms of PD coincide with excessive loss (70-80%) of these neurons.…”
mentioning
confidence: 99%
“…Mutation of parkin was associated with Parkinson's disease [5]. PINK1 drives parkin to locate in mitochondria and interacts with each other to promote mitophagy.…”
Section: Introductionmentioning
confidence: 99%